2015
DOI: 10.1074/jbc.m114.603423
|View full text |Cite
|
Sign up to set email alerts
|

Centrobin-mediated Regulation of the Centrosomal Protein 4.1-associated Protein (CPAP) Level Limits Centriole Length during Elongation Stage

Abstract: Background:The mechanism by which centriole dimensions are regulated is not understood. Results: The absence of centrobin leads to degradation of centrosomal protein 4.1-associated-protein (CPAP). High centrobin levels cause stabilization of CPAP and abnormal centrioles. Conclusion: Centrobin plays a role in the stability and centriole elongation function of CPAP and limits the centriole length. Significance: Identifying the regulatory mechanisms is crucial for understanding centriole biogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 62 publications
1
37
0
1
Order By: Relevance
“…1). The proteins that comprise these appendages are enriched specifically at the mother centriole, whereas the daughter centriole possesses its own specific molecular components (e.g., centrobin-a protein required to ensure the length of the newly formed centrioles; Zou et al 2005;Gudi et al 2015). The current proposed role for distal appendages is in docking the centrosome to the plasma membrane during the formation of cilia (Tanos et al 2013), whereas the subdistal appendages are proposed to act in MTanchoring in interphase cells (Delgehyr et al 2005).…”
Section: Introduction: Centrosomes-small But Not Simplementioning
confidence: 99%
“…1). The proteins that comprise these appendages are enriched specifically at the mother centriole, whereas the daughter centriole possesses its own specific molecular components (e.g., centrobin-a protein required to ensure the length of the newly formed centrioles; Zou et al 2005;Gudi et al 2015). The current proposed role for distal appendages is in docking the centrosome to the plasma membrane during the formation of cilia (Tanos et al 2013), whereas the subdistal appendages are proposed to act in MTanchoring in interphase cells (Delgehyr et al 2005).…”
Section: Introduction: Centrosomes-small But Not Simplementioning
confidence: 99%
“…The role of CPAP in centriole biogenesis and centrosome function is well established (38,41,(48)(49)(50)(51)(52). During our studies to determine the interaction between CPAP and other centriolar proteins, we observed that both HEK293T and HeLa cells transfected with GFP-CPAP showed spontaneous formation of punctate structures.…”
Section: Cpap Overexpression Causes the Formation Of "Mvb-like" Strucmentioning
confidence: 73%
“…Recently, it was reported that centrobin induces centriole elongation through regulating the CPAP level which is also a crucial factor for centriole growth. 15,16 It remains to be investigated what is the biological significance of cytoplasmic centrobin. It is known that both NEK2 and PLK1 phosphorylate centrobin at specific sites but result in opposite outcomes.…”
Section: Discussionmentioning
confidence: 99%